2014
DOI: 10.1007/s00404-014-3275-8
|View full text |Cite
|
Sign up to set email alerts
|

The platelet activating factor acetyl hydrolase, oxidized low-density lipoprotein, paraoxonase 1 and arylesterase levels in treated and untreated patients with polycystic ovary syndrome

Abstract: In patients with PCOS, proatherogenic markers increase. The treatment of PCOS with metformin or Diane-35 had positive effects on lipid profile, increased PON1 level, which is a protector from atherosclerosis and decreased the proatherogenic PAF-AH and ox-LDL levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Further, PON‐1 activity was elevated in women who used oral contraceptives. Although little information is available on this issue, it seems consistent with some other data suggesting that PON‐1 activity is higher in women taking oral contraceptives and may increase in response to ethinyl oestradiol and cyproterone acetate combination …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, PON‐1 activity was elevated in women who used oral contraceptives. Although little information is available on this issue, it seems consistent with some other data suggesting that PON‐1 activity is higher in women taking oral contraceptives and may increase in response to ethinyl oestradiol and cyproterone acetate combination …”
Section: Discussionsupporting
confidence: 82%
“…TSH is logarithmically transformed some other data suggesting that PON-1 activity is higher in women taking oral contraceptives and may increase in response to ethinyl oestradiol and cyproterone acetate combination. 58,59 Several other methodological aspects and limitations of our study need to be considered. We performed a crosssectional study, so that conclusions regarding cause-effect relationships cannot be drawn with certainty.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Cholesterol Education Program guidelines, about 70% of women with PCOS have borderline or high lipid concentrations (Legro et al, 2001). In addition, few studies have reported that oxidized low-density lipoprotein (Ox-LDL) levels as a marker of altered lipid metabolism were significantly higher in untreated PCOS patients than controls (Macut et al, 2006;Carlioglu et al, 2014). Elevated levels of Ox-LDL are associated with the initiation and progression of atherosclerosis (Ehara et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A few groups of investigators have also explored the relationship of these polymorphisms with PCOS and its related traits (23)(24)(25)(26). Treatment with metformin and hormonal supplements (ethinyloestradiol þ cyproterone acetate) has been shown to increase PON1 activity and subsequently decrease oxidative stress in women with PCOS (27,28). However, to our knowledge, no conclusive study exploring the association of PON1 polymorphisms and its activity with PCOS risk, and their relationship with cardiovascular and metabolic dysfunction is available.…”
mentioning
confidence: 99%